Inconspicuous longitudinal tears of the intracranial vertebral artery in traumatic basal subarachnoid hemorrhage - Seongho Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2020)
Blunt force trauma to the head or neck region can cause traumatic basal subarachnoid hemorrhage (TBSAH), which can result in rapid loss of consciousness and death; however, detecting such a vascular injury is difficult. Posterior neck dissection was performed to investigate the bleeding focus in TBSAH cases 2018 and 2019. In all four cases, autopsies revealed a longitudinal tear in the midsection of the vertebral artery's intracranial portion. The midportion of the intracranial vertebral artery appears to be most vulnerable to TBSAH. Interestingly, three of the cases showed only a vaguely visible longitudinal fissure in the artery without a grossly apparent tear; rupture was confirmed by microscopic examination. Longitudinal fissures of the intracranial vertebral artery, which are difficult to identify without detailed examination, may be overlooked in some cases of TBSAH. Thus, careful gross and microscopic examination of the vertebral artery is recommended in cases of TBSAH.